Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have a question which goes like this:

How can I show that $$\sum_{n=1}^{\infty} \frac{z^n}{\left(1-z^n\right)^2} =\sum_{n=1}^\infty \frac{nz^n}{1-z^n}$$ for $|z|<1$?

share|cite|improve this question
Thanks for the info. – Chris Nov 19 '11 at 17:04
up vote 3 down vote accepted

Hint: Try using the expansions $$ \frac{1}{1-x}=1+x+x^2+x^3+x^4+x^5+\dots $$ and $$ \frac{1}{(1-x)^2}=1+2x+3x^2+4x^3+5x^4+\dots $$ Expansion:

$$ \begin{align} \sum_{n=1}^\infty\frac{z^n}{(1-z^n)^2} &=\sum_{n=1}^\infty\sum_{k=0}^\infty(k+1)z^{kn+n}\\ &=\sum_{n=1}^\infty\sum_{k=1}^\infty kz^{kn}\\ &=\sum_{k=1}^\infty\sum_{n=1}^\infty kz^{kn}\\ &=\sum_{k=1}^\infty\sum_{n=0}^\infty kz^{kn+k}\\ &=\sum_{k=1}^\infty\frac{kz^k}{1-z^k} \end{align} $$

share|cite|improve this answer
Thanks for your response. Could you expand more on how to use the hints? – Chris Nov 19 '11 at 17:05
@Chris: Try to plug $x=z^n$ in the $n$th terms of the LHS and of the RHS of the relation you want to prove. – Did Nov 19 '11 at 17:44
That was really hard to enter using the mobile interface. – robjohn Nov 19 '11 at 17:59
@Didier: Thanks – Chris Nov 19 '11 at 19:30
@robjohn: I'm sorry for putting you through the trouble..:) Thanks very much for your help. – Chris Nov 19 '11 at 19:31

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.